Hypocholesteremic effect of bile salt hydrolase from Lactobacillus buchneri ATCC 4005 - Sridevi, N.; Vishwe, Pradnya; Prabhune, Asmita (Food Research International, 2009)
The effect of oral administration of the immobilized bile salt hydrolase enzyme on serum cholesterol. triglyceride, high density lipoprotein levels and its application in the therapeutic treatment of hypercholesteremia was assessed. Culture conditions were optimized for the production of bile salt hydrolase, which resulted in 2.9-fold enhancement in activity. Bile salt hydrolase (BSH; E.C.3.5.1.24) was isolated from Lactobacillus buchneri ATCC 4005 and immobilized in 0.5% gellan gum gel. The immobilized enzyme was orally delivered in wistar rats, induced with hypercholesteremia by triton X-100. The serum cholesterol and triglycerides were reduced by 50% and 15%, respectively, in the group fed with immobilized enzyme 10 IU/kg dose whereas administration of 20 IU/kg immobilized enzyme resulted in reduction of serum cholesterol by 58% and triglycerides by 45%, respectively. The results indicate that bile salt hydrolase has potential cholesterol lowering property and oral administration of the immobilized enzyme is an alternative pharmacological approach to reduce serum cholesterol levels. (C) 2009 Elsevier Ltd. All rights reserved.
International Congress on Bioprocesses in Food Industries, Hyderabad, INDIA, NOV 06-08, 2008
Keywords: Bile salt hydrolase; Gellan gum; Hypocholesteremic effect; Lactobacillus buchneri; Wistar Rats